2013
DOI: 10.1371/journal.pone.0063851
|View full text |Cite
|
Sign up to set email alerts
|

Insulin/IGF-1 Signaling, including Class II/III PI3Ks, β-Arrestin and SGK-1, Is Required in C. elegans to Maintain Pharyngeal Muscle Performance during Starvation

Abstract: In C. elegans, pharyngeal pumping is regulated by the presence of bacteria. In response to food deprivation, the pumping rate rapidly declines by about 50–60%, but then recovers gradually to baseline levels on food after 24 hr. We used this system to study the role of insulin/IGF-1 signaling (IIS) in the recovery of pharyngeal pumping during starvation. Mutant strains with reduced function in the insulin/IGF-1 receptor, DAF-2, various insulins (INS-1 and INS-18), and molecules that regulate insulin release (UN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 88 publications
1
18
0
Order By: Relevance
“…Loss-of-function mutations in the daf-2 gene are associated with constitutive dauer formation (a hibernation-like state of diapause) [26], defects in associative learning [27], and failure to recover pharyngeal pumping during starvation [28]. The latter finding was the starting point for the current studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Loss-of-function mutations in the daf-2 gene are associated with constitutive dauer formation (a hibernation-like state of diapause) [26], defects in associative learning [27], and failure to recover pharyngeal pumping during starvation [28]. The latter finding was the starting point for the current studies.…”
Section: Resultsmentioning
confidence: 99%
“…Two genes, unc-64 and unc-31 , regulate insulin secretion in C. elegans [32], control dauer formation at the restrictive temperature of 27°C [33], and, in the case of unc-64 , affect recovery of pharyngeal pumping during starvation, which requires insulin signaling [28]. UNC-64 (syntaxin) is involved in release from both dense-core vesicles and synaptic vesicles, whereas UNC-31 (Ca ++ -dependent activator protein for secretion, CAPS) mainly regulates release from dense-core vesicles.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it was observed that worms carrying mutations in the gene unc-31, which encodes calcium-activated protein for secretion (CAPS), a calcium-binding protein required for exocytosis (41) pumped constitutively in the absence of food (42). Additional work has investigated C. elegans pharyngeal function in different behavioral contexts and during starvation (4,(43)(44)(45)(46). These suggest a complex shifting behavioral response of the pharyngeal system, which is dependent on the "on" and "off" food context.…”
mentioning
confidence: 99%
“…Previously, we discovered that the NALCN is involved in the recovery of pharyngeal pumping in response to food deprivation, which we attributed to its effects on insulin secretion (Dwyer & Aamodt ). During those studies, we noticed that NALCN‐deficient strains ( nca‐1;nca‐2 , unc‐79 and unc‐80 ) exposed to overnight starvation showed surprising and dramatic improvements in locomotion.…”
mentioning
confidence: 99%